Manipulating Charge‐Transfer Kinetics of Lithium‐Rich Layered Oxide Cathodes in Halide All‐Solid‐State Batteries. Issue 5 (18th December 2022) - Yu, Ruizhi; Wang, Changhong; Duan, Hui; Jiang, Ming; Zhang, Anbang; Fraser, Adam; Zuo, Jiaxuan; Wu, Yanlong; Sun, Yipeng; Zhao, Yang; Liang, Jianwen; Fu, Jiamin; et al.
Abstract: Employing lithium‐rich layered oxide (LLO) as the cathode of all‐solid‐state batteries (ASSBs) is highly desired for realizing high energy density. However, the poor kinetics of LLO, caused by its low electronic conductivity and significant oxygen‐redox‐induced structural degradation, has impeded its application in ASSBs. Here, the charge transfer kinetics of LLO is enhanced by constructing high‐efficiency electron transport networks within solid‐state electrodes, which considerably minimizes electron transfer resistance. In addition, an infusion‐plus‐coating strategy is introduced to stabilize the lattice oxygen of LLO, successfully suppressing the interfacial oxidation of solid electrolyte (Li3 InCl6 ) and structural degradation of LLO. As a result, LLO‐based ASSBs exhibit a high discharge capacity of 230.7 mAh g −1 at 0.1 C and ultra‐long cycle stability over 400 cycles. This work provides an in‐depth understanding of the kinetics of LLO in solid‐state electrodes, and affords a practically feasible strategy to obtain high‐energy‐density ASSBs. Abstract : Lithium‐rich layered oxide (LLO) cathode theoretically enables all‐solid‐state batteries with high energy density owing to its high capacity. However, the low electronic conductivity and highly reactive lattice oxygen impede its application. By introducing conductive additives in electrodes and modifying the surface chemistry of LLO, high‐efficiency electronic networks and stable LLO/electrolyte interfaces can be obtained, thus boosting the charge‐transfer kinetics.